Cladistic analysis and taxonomic review of the millipede tribe Arthrosolaenomeridini Hoffman, 1976 (Polydesmida: Chelodesmidae) - Bouzan, Rodrigo Salvador; Iniesta, Luiz Felipe M.; Brescovit, Antonio Domingos (Zootaxa, 2021)
Chelodesmidae is one of the most diverse families belonging to the Polydesmida, comprising almost 800 described species distributed in 172 genera, 20 tribes and two subfamilies. Among the tribes within the Neotropical subfamily Chelodesminae, Arthrosolaenomeridini represents a very interesting group occurring in the Central-West region of Brazil. Currently the tribe contains three genera: Arthrosolaenomeris Schubart, 1943, Gangugia Schubart, 1947, and Angelodesmus Schubart, 1962. In this study, we conducted a cladistic analysis including 18 species of Arthrosolaenomeridini and 7 species of other associated Chelodesminae tribes as an outgroup. The matrix is composed of 64 morphological characters from which 39 are herein proposed for the first time. The data were analyzed under the parsimony criterion using TNT 1.5. Based on the results, Arthrosolaenomeridini was recovered as monophyletic with Macrocoxodesmini + Telonychopodini as sister group. Arthrosolaenomeris Schubart, 1943 and Gangugia Schubart, 1947 were recovered as monophyletics. The genus Angelodesmus Schubart, 1962 was recovered as paraphyletic and redefined as monotypic. The tribe is now composed of the genera Arthrosolaenomeris (6 spp.), Gangugia (6 spp.), Angelodesmus (monotypic), Abiliodesmus n. gen. (4 spp.) and Folcloredesmus n. gen. (monotypic). In addition, we conduct a taxonomic revision of the tribe Arthrosolaenomeridini providing detailed redescriptions, drawings, and distribution maps for all species and genera, including the two new genera and the ten new species proposed: Arthrosolaenomeris saci n. sp.; A. curupira n. sp.; A. caipora n. sp.; A. iara n. sp.; Gangugia boitata n. sp.; G. cuca n. sp.; G. boto n. sp.; G. mula n. sp.; Abiliodesmus mapinguari n. sp. and Folcloredesmus thomasi n. sp. Furthermore, we include an identification key to all the genera and species.